Penambahan Natrium Bikarbonat pada Pakan Ternak Ruminansia yang Diberi Konsentrat Tinggi terhadap Kecernaan Fraksi Serat Secara in Vitro - Afzalani Afzalani; Rara Amiyati; R.A. Muthalib; Raguati Raguati; Fachroerrozi Hoesni; Rahmi Dianita (Universitas Batanghari Jambi, 2026)
This study aimed to determine the effect of dietary inclusion of sodium bicarbonate (NaHCO3) in high-concentrate ruminant feed on the in vitro digestibility of fiber fractions, including Neutral Detergent Fiber digestibility (NDFD), Acid Detergent Fiber digestibility (ADFD), and hemicellulose digestibility. The experiment was arranged in a Completely Randomized Design (CRD) with 5 treatments and 5 replications. The treatments consisted of: P0 = 20% forage + 80% concentrate + 0% sodium bicarbonate (NaHCO3); P1= P0 + 2.5% (NaHCO3); P2 = P0 + 5% (NaHCO3); P3 = P0 + 7.5% (NaHCO3); and P4 = P0 + 10% (NaHCO3). Duncan's Multiple Range Test (DMRT) was employed to analyze the significant differences among the measured variables. The parameters observed were NDFD, ADFD, and hemicellulose digestibility. The results showed that the addition of NaHCO3 significantly affected (P